2013
DOI: 10.5603/fm.2013.0038
|View full text |Cite
|
Sign up to set email alerts
|

Ossification of the vertebral column in human foetuses: histological and computed tomography studies

Abstract: (Folia Morphol 2013; 72, 3: 230-238)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
(27 reference statements)
1
11
0
3
Order By: Relevance
“…According to these authors, this must have mirrored the sequence of ossification of neural processes that followed caudad. As reported by Skórzewska et al [25], in fetuses aged 10–11 weeks, the neural ossification centers existed within all cervical and upper thoracic vertebrae, and since week 12, they have already been presented in the neural processes of lower thoracic and lumbar vertebrae. However, Bagnall et al [1–3] observed the onset of ossification in the neural processes at the same time in the cervical and thoracolumbar parts, which indubitably contradicted the hypothesis of both cephalad and caudad progressions of ossification in neural processes.…”
Section: Discussionsupporting
confidence: 56%
“…According to these authors, this must have mirrored the sequence of ossification of neural processes that followed caudad. As reported by Skórzewska et al [25], in fetuses aged 10–11 weeks, the neural ossification centers existed within all cervical and upper thoracic vertebrae, and since week 12, they have already been presented in the neural processes of lower thoracic and lumbar vertebrae. However, Bagnall et al [1–3] observed the onset of ossification in the neural processes at the same time in the cervical and thoracolumbar parts, which indubitably contradicted the hypothesis of both cephalad and caudad progressions of ossification in neural processes.…”
Section: Discussionsupporting
confidence: 56%
“…Evidence for ossification of the neural arches has been documented as early as 9 weeks of gestation in the cervical regions and progresses in the cranial-to-caudal direction. 32 The neurocentral synchondrosis delineates the junction where the centrum and both arch centers fuse.…”
mentioning
confidence: 99%
“…According to these authors, the commencement of ossification in neural arches might be both a consequence of fetal movements and the influence of particular skeletal muscles. Skórzewska et al [20] found vertebrae to start to ossify in fetuses aged 10–11 weeks. Firstly, ossification centers appeared within the neural arches of the cervical and upper thoracic vertebrae, and 1 week later were also present in the arches of the successive thoracic and lumbar vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…The first vertebral body ossification centers occur in the arches of upper cervical vertebrae, as early as at week 8 in the axis, and then progress caudad [6]. The first vertebral body ossification centers occur at week 10 in lower thoracic vertebrae and the first lumbar vertebra, from which the process continues both cephalad and caudad [20]. …”
Section: Introductionmentioning
confidence: 99%